(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study included 28 local isolates with standard isolation B.t.kurstaki. The statistical analysis of the results of bio-evaluation on the Ephestia cautella larvae showed that the standard isolation B.t.kurstaki gave very high killing results of 100% at the first concentration of 1.2 × 106 spor / g after ten days of treatment superior to All isolates were followed by isolation of IN-1, which resulted in a 90% kill with a concentration of 1.2 × 106 spor / g followed by isolation of NJ-1, killing 73.3% at a concentration of 1.2 × 106 spor / g. Cry1 was found in the standard isolation B.t.kurstaki and the local isolation NJ-1, where the size of the gene was 260-280bp. The isolation of the NJ-1 was found to be serovar B.t.kurstaki. When we used the Cry9 gene, we obtained this gene in local isolation, IN-1, and we did not obtain this gene in the other isolates, as the size of the gene was 345-360 bp, and it was shown that the isolation was serovar B.t.aizawai.